Methods and validity indicators for measuring adherence to statins in secondary cardiovascular prevention: a systematic review - Adriana López-Pineda; María Martinez-Muñoz; Rauf Nouni-García; Amanda Esquerdo-Arroyo; Álvaro Carbonell-Soliva; Elizabeth Ramirez-Familia; Mª Isabel Tomás-Rodríguez; Jose A. Quesada; Concepción Carratalá-Munuera C; Vicente F. Gil-Guillén (Systematic Reviews)
Abstract Background Adherence to statin therapy is crucial for reducing the recurrence of cardiovascular events. Numerous methods exist to measure medication adherence, including those based on prescription data, patient self-report, medication counting, and direct methods. It is important to determine which of these methods are appropriate for use in clinical practice. This systematic review aimed to identify the methods used to measure adherence and persistence to statins in patients undergoing cardiovascular secondary prevention and to evaluate the validity indicators of these methods. Methods This systematic review included studies reporting methods to measure adherence and/or persistence to statins in cardiovascular secondary prevention. Medline, Embase, and Scopus databases were searched from inception to February 2025. Rayyan was used for the study selection and extraction data processes. Validity indicators of the adherence/persistence methods were collected; it was reported. Risk of bias of studies reporting the method validity was evaluated using the COSMIN (Consensus-based Standards for the Selection of Health Measurement Instruments) tool. Results A total of 77 studies were included. Regarding adherence measurement, the most frequently used method was prescription refill records (n = 55) and self-report methods (n = 20). Electronic monitoring methods (n = 2), self-perceived adherence by physician (n = 1), and pill counting (n = 1) were less frequently used methods. Direct methods, using HPLC–MS/MS, were used in combination with other indirect methods (n = 5). For measuring persistence, prescription refill records were the predominant method (n = 9), while self-report methods were used in three studies, and one study used a standardized questionnaire. Several of the indirect methods have validity indicators for measuring adherence in different study populations and to different medications. Only one study provides validity indicators for the MAT questionnaire specifically adapted for statins. Conclusions The methods for measuring adherence to statins in secondary cardiovascular prevention were predominantly indirect, relying on prescription and supply records and self-report methods. Pill counting, electronic monitoring, and direct measurement via LC–MS/MS were less commonly used. Persistence was primarily measured through prescription refill records. None of the indirect methods was validated; thus, their use for measuring adherence to statins is not recommended. There is a need for new validated tools, incorporating a gender perspective, to measure adherence to statins in this population. Systematic review registration PROSPERO CRD42023463981.